Prediction of Quality of Life in Asian Patients with Schizophrenia: A Cross-sectional Pilot Study - Choo, Carol C.; Chew, Peter K. H.; Ho, Cyrus S.; Ho, Roger C. (Frontiers in Psychiatry, 2017)
Background: There has been a shift in mental health services from an emphasis on treatment focused on reducing symptoms to a more holistic approach involving quality of life (QOL) and overall well-being. Many psychosocial variables are associated with QOL but a parsimonious framework is needed to deepen our understanding about the contribution of psychosocial factors in influencing the QOL of Asian patients with schizophrenia in Singapore. The study aimed to address the current gap in literature by analysis of QOL using available predictors in Asian patients with schizophrenia in Singapore. Methods: 43 Singaporean patients diagnosed with schizophrenia were recruited at a large teaching hospital in Singapore from January to May 2010 and were invited to complete questionnaires. Of the sample, 65.1% were females, ages ranged from 18 to 65 (M = 44.60, SD = 12.19). Available variables were subjected to regression analysis. Findings: The data were analysed using SPSS Version 23 with the alpha level set at .05. The final model with 5 predictors was significant in predicting QOL. Positive Re-appraisal, Social Support, Avoidant Coping, Duration of Hospitalization, and Education accounted for 47.2% of the variance (Adjusted R2 = 40.0%) in QOL, F (5, 37) = 6.60, p < .001. Those with post-secondary or higher education had higher QOL than those with secondary or lower education. Duration of hospitalization negatively predicted QOL. Conclusions: The findings were discussed in regards to clinical implications for informing interventions to enhance QOL in patients with schizophrenia.